HTM:a new hierarchical interconnection network for future generation parallel computers - Rahman, M.M. Hafizur; Shah, Asadullah; Fukushi, Masaru; Inoguchi, Yasushi (Medknow publication, 2016)
In this paper, we have discussed the architectural structure, static network performance and dynamic communication performance of a new hierarchical interconnection network called Hierarchical Tori connected Mesh Network (HTM). For the exploration of static network performance, we have evaluated degree, diameter, cost, average distance, arc-connectivity, bisection width, and wiring complexity. We have also evaluated the dynamic communication performance of HTM, its counter rival H3DM, and conventional mesh & torus networks using a deadlock-free dimension order routing using $2$ virtual channels under uniform and non-uniform traffic patterns. The dynamic communication performance is evaluated using computer simulation. We discovered that the HTM has a number of lucrative properties. These include constant node degree, small diameter, low cost, small average distance, moderate (neither too low, nor too high) bisection width, less wiring complexity. HTM also yields high throughput per link and very low zero load latency, which provide better dynamic communication performance than that of H3DM, mesh, and torus networks.